Recent Progress in Graphene/Polymer Nanocomposites. Issue 6 (6th September 2020) - Sun, Xianxian; Huang, Chuanjin; Wang, Lidong; Liang, Lei; Cheng, Yuanjing; Fei, Weidong; Li, Yibin
Abstract: Nanocomposites, multiphase solid materials with at least one nanoscaled component, have been attracting ever‐increasing attention because of their unique properties. Graphene is an ideal filler for high‐performance multifunctional nanocomposites in light of its superior mechanical, electrical, thermal, and optical properties. However, the 2D nature of graphene usually gives rise to highly anisotropic features, which brings new opportunities to tailor nanocomposites by making full use of its excellent in‐plane properties. Here, recent progress on graphene/polymer nanocomposites is summarized with emphasis on strengthening/toughening, electrical conduction, thermal transportation, and photothermal energy conversion. The influence of the graphene configuration, including layer number, defects, and lateral size, on its intrinsic properties and the properties of graphene/polymer nanocomposites is systematically analyzed. Meanwhile, the role of the interfacial interaction between graphene and polymer in affecting the properties of nanocomposites is also explored. The correlation between the graphene distribution in the matrix and the properties of the nanocomposite is discussed in detail. The key challenges and possible solutions are also addressed. This review may provide a constructive guidance for preparing high‐performance graphene/polymer nanocomposite in the future. Abstract : Recent progress on graphene/polymer nanocomposites is reviewed, with emphasis on strengthening and toughening, electrical conduction, thermal transportation, and photothermal conversion. The roles of graphene configuration, interfacial interaction, and distribution of graphene in the polymer to determine the properties of the nanocomposites are systematically explored. This may provide constructive guidance to develop high‐performance nanocomposites in the future.